ABDOMINAL STRETCHING TRAINING IMPROVES KNOWLEDGE OF DYSMENORRHEA PREVENTION IN ADOLESCENTS - Emdat Suprayitno; Dian Permatasari; Rasyidah Rasyidah; Cory Nelia Damayanti; Eka Meiri Kurniyati (Poltekkes Kemenkes Surakarta, 2022)
Background: Menstruation is a physiological thing that happens to all young women. However, many women experience menstrual problems, including menstrual pain and dysmenorrhea. Most menstrual pain occurs during adolescence and is related to limited physical activity and absence from school or work. Therefore, attention should be paid to adolescent dysmenorrhea and appropriate nonpharmacological treatment. This program aims to educate young women about dysmenorrhea by providing appropriate nonpharmacological interventions, especially for abdominal distension. Methods: The location of this activity is Man1 Sumenep. The number of participants in this activity was 36. This education and abdominal stretching exercise are done only once with the lecture and question and answer method for 90 minutes. The post-test was carried out at the end of the event after education and training were carried out using a questionnaire. The P value was obtained based on data analysis using the Wilcoxon signed rank test, namely: 0.001. Results: There was a significant difference in the proportion of pain intensity after intervention in the intervention group. Abdominal stretching exercise is one of the non-pharmacological management methods that are safe to do and has been widely used to reduce the symptoms of primary dysmenorrhea. Conclusion: It can be concluded that education and abdominal stretching exercises effectively increase knowledge of dysmenorrhea prevention in young women. It is hoped that young women will be able to manage their dysmenorrhea so that they remain active and carry out their daily activities at school or home.